Productivity of experimental sugar beet hybrids created on the base the improved sterile form and multiseminal pollinators - Парій, Ф. М.; Андрощук, М. П.; Труш, С. Г. (Scientific Progress & Innovations, 2012)
Studying of parent components is an important direction for research. Using МС 94 line as a mother form makes it possible to create geterosis hybrids with high productivity. The authors investigated the influence of the improved in the complex of selection-genetic features sterile line as to their commercially valuable characteristics in the process of creating sugar beet hybrids. Testing of the received hybrids was conducted and their productivity indices were evaluated. MС 94 line is recommended to be involved in the selection process for the formation of highly productive sugar beet hybrids of new generation.